nalyses on CH4 and CO2 hydrate formation to define the optimal pressure for CO2 injection to maximize the replacement efficiency into natural gas hydrate in presence of a silica-based natural porous medium, via depressurization techniques - Alberto Maria Gambelli (2021)
To make natural gas hydrate an energy source available for large-scale applications, some issues must be solved; amongst them, the low kinetic characterizing the process and re-formation of methane hydrate are the most significant. In this paper methane and carbon dioxide hydrate formation was tested in presence of a natural silica-based porous sand, with the aim of define the most useful pressure value for carbon dioxide injection into reservoirs in order to apply replacement strategies via depressurization. A direct comparison between CO2 hydrate formation tests starting respectively from 30 bar and 40 bar, revealed that this latter solution represents the most effective solution. While moles of CO2 involved into hydrate and, more in general, moles of CO2 permanently stored, are similar in both typologies of tests, the time necessary to complete the formation process was drastically lower in tests started from 40 bar. Moreover, a lower pressure drop would be required. The more effective kinetic of the process and the negligible risk of methane hydrate re-formation verified during experiments, allowed to consider the CO2 injection into the reservoir at 40 bar the best solution to optimize methane recovery, carbon dioxide storage and seafloor deformations due to the reservoir exploitation.